R (−)-methoxetamine exerts rapid and sustained antidepressant effects and fewer behavioral side effects relative to S (+)-methoxetamine. (1st August 2021) - Botanas, Chrislean Jun; Perez Custodio, Raly James; Kim, Hee Jin; de la Pena, June Bryan; Sayson, Leandro Val; Ortiz, Darlene Mae; Kim, Mikyung; Lee, Hyun Jun; Acharya, Srijan; Kim, Kyeong-Man; Lee, Cheol Jung; Ryu, Jong Hoon; et al.
Abstract: The newfound antidepressant efficacy of ketamine has provided opportunities for the development of new-generation, rapid-acting, glutamate-based antidepressants. We previously identified that methoxetamine (MXE), a ketamine analog, and an N -Methyl-d -aspartate (NMDA) receptor antagonist, produced rapid and sustained antidepressant effects in mice. MXE ( R, S (±)-MXE) is a racemic mixture containing equal parts of S (+)-MXE and R (−)-MXE. However, studies have yet to investigate the antidepressant effects of its enantiomers. Here, we examined the potential antidepressant properties and behavioral side effects of S- and R- MXE in mice. Both S- and R- MXE showed significant NMDA receptor affinity and appreciable inhibitory activity on serotonin transporter. Also, S- and R- MXE (10 mg kg −1 ) exerted antidepressant effects and increased gamma waves (electroencephalography) but were inhibited by NBQX (an AMPA receptor antagonist). Subsequently, they increased mammalian target of rapamycin phosphorylation and AMPA receptor subunits GluA1 and GluA2 protein levels in the hippocampus or prefrontal cortex. Furthermore, they increased 5HT2a and 5HT2c receptor mRNA levels in the prefrontal cortex, with their antidepressant effects inhibited by ketanserin (a 5HT2a/c receptor antagonist). Taken together, S- MXE and R- MXE elicit antidepressant effects that are probably mediated via glutamatergic and serotonergic mechanisms. Unlike S- MXE, R- MXE did not induce prepulse inhibition deficits, hyperlocomotion, conditioned place preference, and locomotor sensitization, although it acutely altered motor coordination. This suggests that R- MXE induces fewer behavioral side effects and is a safer antidepressant than S- MXE. Overall, this study provides significant implications for future research on the next generation of rapid-acting, glutamate-based antidepressant drugs. Graphical abstract: Image 1 Highlights: S -MXE and R -MXE induce rapid and sustained antidepressant effects in mice. The antidepressant effects of the MXE enantiomers are probably via the glutamatergic and serotonergic mechanisms. Unlike MXE racemate and S- MXE, R -MXE did not induce PPI deficits, hyperlocomotion, CPP, and locomotor sensitization.